PENGARUH PEMBERIAN KOMPOS ECENG GONDOK DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascaloicum L.) - Hendrawan Hs Hendrawan Hs; Arnis En Yulia2; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aims of this research were to best out the effect of water hyacinth compost aplication and plantdistance, and to got dose of water hyacinthcompost toward growth and production of union. This research was conducted at the technical plantation unit of experimental garden of Riau University's Agricultural Faculty from August to November 2017 using factorial arranged in randomized block design consists of 2 factors and 3 replications. The first factor of water hyacinthcompost are 10 ton.haˉ¹, 15 ton.haˉ¹, 20 ton.haˉ¹, and 25 ton.haˉ¹. The second factor planting distanceis 10 cm x 20 cm, 15 cm x 20 cm and 20 cm x 20 cm. The data obtained were tested further by Duncan's multiple-range test of 5%.The interaction of water hyacinthcomposting andplanting distance no significant effect on all observation parameters. The interaction of water hyacinthcomposti doses 25 ton.ha-¹ at plant spacing of 15 cm x 20 cm appears to be the best dose to increase leaf count per clump, tuber bulbs, and tuber weight per plot of red onion. Keywords:Onion, compost, planting distance